Household Gods - Pilikian, Vaughan (United Kingdom : Unruowe, 2008)
Alone at home, but haunted by other voices: six people in six rooms somewhere in London are scrutinized. The film records the expressions on their faces and the sounds that swirl around them. What are these sounds? In earlier times the house was a holy place, with shrines and trinkets set about it to protect it from evil influences. In this film, each of the scenes is ‘possessed’ by insubstantial, incorporeal voices: by the invaders of the mass media. In the present day, where are the household gods that protect the home? And what form do its demons take?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films